2023
DOI: 10.3389/fmicb.2023.1063807
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oestrus synchronization devices on ewes vaginal microbiota and artificial insemination outcome

Abstract: IntroductionThe low pregnancy rate by artificial insemination in sheep represents a fundamental challenge for breeding programs. In this species, oestrus synchronization is carried out by manipulating hormonal regimens through the insertion of progestogen intravaginal devices. This reproductive strategy may alter the vaginal microbiota affecting the artificial insemination outcome.MethodsIn this study, we analyzed the vaginal microbiome of 94 vaginal swabs collected from 47 ewes with alternative treatments app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 81 publications
2
11
0
Order By: Relevance
“…Since Ma has the ability to colonize the mammary gland and the vagina [ 9 ] and LAB and Staphylococcus spp. seem to be part of the microbiota of these anatomical sites [ 18 , 19 , 20 , 25 , 50 ], the present study describes the in vitro interactions between Ma and wild strains of CNS and Enterococcus spp. isolated from raw milk and vagina, respectively, of clinically healthy small ruminants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since Ma has the ability to colonize the mammary gland and the vagina [ 9 ] and LAB and Staphylococcus spp. seem to be part of the microbiota of these anatomical sites [ 18 , 19 , 20 , 25 , 50 ], the present study describes the in vitro interactions between Ma and wild strains of CNS and Enterococcus spp. isolated from raw milk and vagina, respectively, of clinically healthy small ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, this offers a favorable environment for Ma and suggests that the vagina could represent a possible ecological niche of Ma in small ruminants. Indeed, the genus Mycoplasma has recently been described as the second most abundant in the vagina of ewes [ 20 ]. Although the presence of LAB in the vagina of small ruminants seems sparse, their use and the necessity to study them have been suggested in small ruminants due to their well-known antimicrobial potential [ 18 , 20 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the sponges also worked to homogenize the populations of bacteria present regardless of the point in the ewe’s estrous cycle when the sponge was inserted ( Manes et al, 2010 ; Gatti et al, 2011 ; Martinez-Ros et al, 2018 ; Quereda et al, 2020 ). Other studies evaluated the vaginal microbiota of sheep using an alternate method – 16S rRNA gene sequencing ( Swartz et al, 2014 ; Serrano et al, 2020 ; Koester et al, 2021 ; Greenwood et al, 2022 ; Reinoso-Peláez et al, 2023 ). One of those studies ( Koester et al, 2021 ) was conducted in our laboratory and was based on three sampling time points.…”
Section: Introductionmentioning
confidence: 99%